Estimation of Age of Abrasion by Gross Examination at Autopsy: A Cross-Sectional Study (Indian Journal of Forensic Medicine & Toxicology, 2023)
Background: One of the most important aspects of medicolegal injury examination is the determination of the ageof the injury. This study of wound dating from the gross examination of abrasion is being conducted to look intothe accuracy of dating the wounds by the age determined by gross changes with that of the time of infliction ofinjury.Methods: In this cross-sectional study, 102 dead bodies brought for medicolegal autopsy, having a well demarcatedabrasion and a known time of infliction of injury were selected. Based on the duration of infliction, abrasions werecategorized into 13 groups. Gross changes that follow blunt trauma were studied and correlated to the time frameof the occurrence of abrasion.Conclusion: A significant relationship between the age and color of abrasion (X272=387.59, P2 weeks).
Keywords: Abrasion; Age of abrasions; Autopsy; Gross change